Alejandra Amatto y Alejandro Toledo (coords.), ConversaTario. Ensayos en torno a Francisco Tario. Universidad Autónoma de Querétaro, Querétaro, 2021; 445 pp. - Luis Alcázar, Sergio Javier (El Colegio de México, 2025)
Es una reseña